PERKEMBANGAN PEMANFAATAN, REGULASI, DAN METODE DETEKSI PRODUK REKAYASA GENETIKA PERTANIAN DI INDONESIA / Development of Utilization, Regulation, and Detection Methods of Agricultural Genetically Modified Products in Indonesia - Bahagiawati Bahagiawati; Toto Hadiarto (Jurnal Penelitian dan Pengembangan Pertanian, 2020)
Genetically modified crops (GM crops) have developed very fast globally, although to date controversies over the GM crop uses are still occurring. GM crops have been planted on over 191.7 million hectare area and cultivated in 26 countries in five continents. Biosafety of GM crops both globally and domestically are guaranteed through regulations made at the level of law, government regulations, related ministrial regulation including the guidelines. In general, those regulations have been implemented, thus the biosafety of GM crop utilization is guaranteed in Indonesia. Unfortunately, although Indonesia gave a certification for released permit for drought tolerant sugarcane, it only grown in a limited areas belongs to state-owned agricultural company (PTPN XI). The country has certified 27, 7, and 16 GM events for food, feed, and seeds for environment safety, respectively. The implementation of these regulations needs a monitoring system that is equipped with facilities of GMO detection laboratory with adequate capacity. Indonesia has several such laboratories. The methods of GMO detections have developed from very basic techniques, i.e. qualitative screening to the determination of specific events that define the type of trait of GMO, even quantitative detection, both single and multiplex. Each method has its own advantages. The capacities of GMO detection laboratory in Indonesia still need to be upgraded to master the fast-developing technology. The purpose of this review is to provide information on the development of global GM crops utilization including in Indonesia and the development of regulations and detection methods with their prospects and challenges.Keywords: Genetics, modification, regulation, detection methods AbstrakPemanfaatan tanaman produk rekayasa genetik (PRG) telah berkembang cepat dan mendunia walaupun sampai saat ini masih terjadi kontroversi. Luas penanamannya telah mencapai 191,7 juta ha dan ditanam oleh 26 negara di lima benua. Keamanan hayati PRG secara global maupun domestik telah dijamin oleh peraturan pada tingkat undang-undang, peraturan pemerintah, peraturan kementerian terkait, dan pedoman pelaksanaannya. Secara umum peraturan peraturan tersebut telah dijalankan sehingga keamanan hayati dari pemanfaatan PRG terjamin di Indonesia. Sayangnya di Indonesia PRG yang sudah diberi izin edar hanya ditanam secara terbatas seperti tebu toleran kekeringan di beberapa kebun milik PTPN. Indonesia juga telah memberikan sertifikat aman hayati pada beberapa varietas PRG diantaranya 27 PRG pangan, tujuh PRG pakan, dan 16 PRG benih (lingkungan). Implementasi peraturan yang telah ada memerlukan sistem pengawasan yang dilengkapi dengan fasilitas laboratorium deteksi PRG dengan kapasitas yang memadai. Indonesia telah mempunyai beberapa laboratorium tersebut. Metode deteksi PRG telah berkembang dari teknik yang sangat mendasar yaitu deteksi untuk skrining kualitatif PRG sampai teknik penentuan spesifik event yang menetapkan jenis/sifat PRG, bahkan teknik deteksi secara kuantitatif yang bersifat tunggal maupun multiplex. Metode-metode deteksi tersebut memiliki keunggulan masing-masing. Laboratorium penguji PRG di Indonesia masih perlu ditingkatkan kemampuannya dengan penguasaan teknologi yang berkembang dengan pesat. Makalah ini memberikan informasi perkembangan pemanfaatan PRG global termasuk di Indonesia dan perkembangan regulasi dan metode deteksi serta prospek dan tantangan.Kata kunci: Genetika, rekayasa, regulasi, metode deteksi